Evaluation of Antibacterial Activity of Aqueous Extracts of Pomegranate Peels, Green Tea Leaves and Bay Leaves against Vibrio cholera - Al-Dhaher, Zainab A. (The Iraqi Journal of Veterinary Medicine, 2013)
The antibacterial activity of aqueous extracts of Pomegranate peels, Green tea leaves, Bay leaves were evaluated in this study. Agar diffusion technique was applied. The three extracts were found to have inhibitory effect against Vibrio cholera and the mean of the diameter of inhibition zones ranges from (11-23 mm) for pomegranate peels, (9-20 mm) for Green tea leaves and (718mm) for Bay leaves extracts and statistically analyzed. There were significant differences between pomegranate peels, tea leaves and bay leaves extracts at each concentration used in this study. The pomegranate peels were found to have greater effects against Vibrio cholera followed by tea leaves, Bay leaves. Minimum bactericidal concentration (MBC) was also determined and it was shown that 10mg/ml was the MBC for pomegranate peels, 10-15mg/ml the MBC for tea leaves and 20-25mg/ml the MBC for Bay leaves.